2019
DOI: 10.1136/ijgc-2018-000148
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two alternative ablation treatments for cervical pre-cancer against standard gas-based cryotherapy: a randomized non-inferiority study

Abstract: IntroductionGas-based cryotherapy is the conventional ablative treatment for cervical pre-cancer in low-income settings, but the use of gas poses significant challenges. We compared the depth of necrosis induced by gas-based cryotherapy with two gas-free alternatives: cryotherapy using CryoPen,and thermoablation.MethodsWe conducted a five-arm randomized non-inferiority trial: double-freeze carbon dioxide (CO2) cryotherapy (referent), single-freeze CO2 cryotherapy, double-freeze CryoPen, single-freeze CryoPen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Our findings are in line with the results of a clinical study conducted in Peru and El Salvador where patients planned for hysterectomy for benign indication were treated with cryotherapy or thermal ablation one day in advance [19]. This study evaluated the tissue necrosis depth 24 to 48 h after initial treatment.…”
Section: Interpretation Of Resultssupporting
confidence: 88%
“…Our findings are in line with the results of a clinical study conducted in Peru and El Salvador where patients planned for hysterectomy for benign indication were treated with cryotherapy or thermal ablation one day in advance [19]. This study evaluated the tissue necrosis depth 24 to 48 h after initial treatment.…”
Section: Interpretation Of Resultssupporting
confidence: 88%
“…On the other hand, ablative methods destroy the TZ by freezing the epithelium down to −80°C (cryotherapy) or by heating the epithelium to 100°C (thermal ablation), causing tissue necrosis. Tissue necrosis following cold or heat injury is expected to ensure the treatment of high‐grade lesions extending to the crypts, although some studies have questioned the adequacy of the depth of treatment achieved following thermal ablation 30,31 . An inability to identify the squamocolumnar junction correctly, and hence a failure to select appropriate cases for ablation, may be another reason for the variability in treatment outcomes after ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that superficial CO 2 cryotherapy achieved an average necrotic depth of 3.4 mm 24 hours after ablation, 90 , 91 while others reported depths of 6 mm 48 hours after ablation. 92 Although CIN1 and 2 can be adequately treated with shallower depths (2-4 mm), CIN3 and CIN extending into the endocervical canal require deeper depths (≥4.8 mm). 90 , 91 Because of the conflicting evidence, 93 it remains unclear if superficial cryotherapy can adequately treat more advanced CIN.…”
Section: Cryotherapymentioning
confidence: 99%